FIXED POINTS IN MENGER SPACE FOR WEAK COMPATIBLE MAPPINGS - Jain, Dr. Arihant; Gupta, V. K.; Bhinde, Ramesh (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The purpose of this paper is to establish a unique common fixed point theorem for six self mappings using the concept of weak compatibility in Menger space which is an alternate result of Jain and Singh [5]. We also cited an example in support of our result.